Tomographic imaging of fragmented cortical bone heteroimplant and methylmethacrylate in segmental bone defect of rabbit tibia1 - De Freitas, Silvio Henrique; Dória, Renata Gebara Sampaio; De Souza Mendonça, Fábio; Dos Santos, Marcelo Diniz; Filho, Jair Rodini EngráCia [UNESP]; Vidane, AtanáSio Serafim; Marques, Alessandro Tadeu Corrêa; Ambrósio, Carlos Eduardo (FapUNIFESP (SciELO), 2014)
PURPOSE: To evaluate the performance of composites consisting of fragmented cortical bone heteroimplant in association with methylmethacrylate preserved in 98% glycerin, in segmental bone defect of rabbit tibia medial metaphysis. METHODS: In this study were used twelve adult New Zealand rabbits, divided into three groups of four animals each: G30 (30 days), G60 (60 days) and G90 (90 days). The bone defects previously created in the tibia were filled with composites and both were evaluated by cone-beam computed tomography, immediately after surgery and after 30, 60, and 90 days. RESULTS: The composites fulfilled and remained in the sites of bone defects in all cases and were not registered signals of infection, migration or rejection. CONCLUSIONS: The implanted composites promoted the bone defects repair without signals of infection and/or rejection. The composites are one more option for bone defects repair.
Keywords: Biocompatible Materials; Rabbits; Tibia; Tomography